Alteraciones neurológicas e inmunosupresión en pacientes con trasplante renal. Estudio preliminar - Chasity Romero-Vázquez (Revista Alergia México, 2016)
Background: Neurological disorders in kidney transplant patients may be related to several factors, including high toxicity to the use of immunosuppressive drugs. Objective: To find out whether there was association between neurological complications and immunosuppression in a sample of patients who received renal transplantation. Methods: Cross-sectional study in which 121 renal transplant patients participated, of which 22 (18%) had neurological disorders, χ 2 was used to analyze the relation between neurological disorders and comorbidity such as diabetes mellitus and hypertension and time of immunosuppressant use. A significance level of p <0.05 was accepted for all determinations Results: Of the subjects studied, 13 were male (59%) and nine female (41%). The mean age of the patients included in the study was 33 ± 12 years. 59% of neurological disorders occurred between six months and five years after patients had received the transplant. Neurological alterations found were: tremor (7.4%), dizziness (4.1%), peripheral neuropathy (3.3%), headache (2.4%), and decreased strength (0.8%). Conclusion: No statistically significant association was found between neurological disorders and immunosuppressant use, or between them and the duration of immunosuppression.